Synthetic, Spectral and Thermal Studies of Tin(IV) Complexes of 1, 5-Benzodiazepines - Suresh; Padaki Srinivas; T. Suresh; M. Revanasiddappa; Syed Khasim (E-Journal of Chemistry)
Tin(IV) complexes of 7-substituted 6,7-benzo-1,5-dizepines have been synthesized in absolute alcoholic medium. Elemental analysis indicates that the complexes have 1:2 stoichiometry of the type L2SnCl4, TGA data support this conclusion. Molar conductance values in DMF at 10–3 M suggest that, these complexes are non-electrolytes. Infrared spectral data shows the involvement of C=N and NH groups in coordination with the metal ion. X-ray diffraction pattern of few representative complexes indicate that, these are having simple cubic crystal structure. The energy of activation and order of reaction are calculated using TGA data of the complexes. All these information support that Sn(IV) in these complexes exhibits coordination number eight.